Physiological, biochemical and HSP70 and HSP90 gene expression profiles of tropical abalone Haliotis squamata in response to Vibrio alginolyticus infection - Ngurah S. Yasa; Murwantoko Murwantoko; Niken S. N. Handayani; Gemi Triastutik; Lutfi Anshory (Universitas Gadjah Mada, 2020)
Vibrio spp. have been known responsible for fish diseases in marine and brackish‐water systems in the tropics regions. Heat shock proteins are a highly conserved protein group that is known for its rapid response to environmental stresses, including infection. This study aimed to investigate physiological and biochemical responses of tropical abalone Haliotis squamata to Vibrio alginolyticus infection. Abalones were infected with V. alginolyticus by intramuscular injection at a dose of 105,106,107 cfu/abalone. The expression of HSP70 and HSP90 genes, the activity of superoxide dismutase, phenol oxidase and catalase enzymes, histology, falling and mortality were observed at 12, 24, 48, 72, and 96 hours post‐infection (hpi). The different expression of HSPs was found in this study. While the expression of HSP70 was downregulated after infection, the expression of HSP90 was upregulated at 12 hpi and followed by downregulated after 24 hpi for 106 cfu infection, but expressed at a normal level for 105 infection treatment. The expression ofsuperoxide dismutase and catalase increased within 12 hpi, and the expression of phenol oxidase increased after 24 hpi. V. alginolyticus is virulent with LD50 of less than 105 cfu on H. squamata with an average weight of 5.13 g, and caused enlargement of hemolymph sinus and development intraepithelial and intramuscular abscesses.